1995
DOI: 10.1002/jsfa.2740670316
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the role played by fermentation esters in the aroma of young Spanish wines by multivariate analysis

Abstract: The role played by ethyl esters of fatty acids and by acetates of higher alcohols on the aroma of young wines from neutral grape varieties has been investigated. The statistical methods used have been stepwise linear regression and principal components analysis. Very significant conclusions have been reached. The role played by these compounds depends on the type of wine. In white wines their main role is in the perception of tree fruit and tropical fruit notes. It has been demonstrated that the former notes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(103 citation statements)
references
References 12 publications
5
85
0
4
Order By: Relevance
“…However, CDY showed a limited persistence (33 days) compared to GR1 which lasted until the 51st day. During fermentation, yeasts produced a wide variety of secondary products (alcohols, esters, acids, aldehydes, ketones, lactones, terpenoids and phenols) that contribute significantly, especially higher alcohols and esters (Ferreira et al 1995), to the sensory properties of wines. The differences between fermentation by GR1 and CDY were first in terms of VOC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, CDY showed a limited persistence (33 days) compared to GR1 which lasted until the 51st day. During fermentation, yeasts produced a wide variety of secondary products (alcohols, esters, acids, aldehydes, ketones, lactones, terpenoids and phenols) that contribute significantly, especially higher alcohols and esters (Ferreira et al 1995), to the sensory properties of wines. The differences between fermentation by GR1 and CDY were first in terms of VOC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Both ethyl hexanoate and octanoate had been previously reported as major contributors to the flavor of Vidal wine [9]. Ferreira and coworkers showed that fatty acid ethyl esters play a significant role in the delicate aroma of white wines [40].…”
Section: Fatty Acid Ethyl Esters and Free Fatty Acidsmentioning
confidence: 99%
“…This is because, as we have written in the section 3.5., the higher nitrogen concentration in the initial must, the less alcohol synthesis during the alcoholic fermentation (Torrea et al, 2003;Ugliano & Henschke, 2009;Vilanova et al, 2007). Esters are very important compounds on wine quality, as they are the main compounds responsible for the fruity and floral character in wines (Ferreira et al, 1995;Franciolo et al, 2003). All the esters studied showed higher concentration for Monastrell non-organic wines, (Figure 4).…”
Section: Consumption Of Amino Acids During the Alcoholic Fermentationmentioning
confidence: 99%